Development And Quality Evaluation Of Low-Fat Chicken Nuggets Incorporated With Brown Rice Flour - kumar, K Ajay; Gupta, R S Dilip; Devathkal, S K; Rao, B Eswara; subhasini, N (Journal of Meat Science, 2024)
Chicken nuggets prepared by incorporating three different levels of brown rice flour along with other non-meat ingredients. The formulations prepared were – Control (0% brown rice flour), T1(2% brown rice flour), T2(4% Brown rice flour), T3(6% Brown rice flour). Among different treatments, brown rice flour at 6% produced significantly (P<0.05) higher emulsion stability, water holding capacity, pH and better sensory scores than rest of the formulations. Proximate composition of the study revealed significant (P<0.05) increase in moisture, protein, fiber and ash content. The texture profile analysis studies revealed a significant(P<0.05) increase in some parameters, which are gumminess, springiness and cohesiveness. The microbiological studies revealed that products were acceptable up to 9 days. Based on the results obtained in the study it might be concluded that chicken nuggets could be prepared satisfactorily on addition up to 6% brown rice flour without adverse effect on the quality of the products.